PENINGKATAN KESADARAN HUKUM BAGI MASYARAKAT MELALUI PENDAMPINGAN PENYULUHAN HUKUM DIKELURAHAN KAYU OMBUN PADANGSIDIMPUAN UTARA - Agustina Damanik; Sawaluddin Siregar (Yayasan Baitul Hikmah al-Zain, 2024)
Community service in Legal Aid assistance is carried out to introduce how the law actually applies in society. Where participatory community service activities or participatory real appraisal is an approach method in the process, from the activities to be carried out, namely regarding legal counseling. Legal counseling is a routine program of the Faculty of Sharia and Law at UIN Syeihk Ali Hasan Ahmad Addady Padangsidimpuan which is held every semester. This year's legal counseling was held in the Kayu Ombun Village, North Padangsidimpuan District. At least six topics were presented in the legal counselling, including drug control, trafficking, domestic violence (domestic violence), disaster, legal drafting, national insights and defending the country. This legal counseling was attended by village government officials, community leaders, and also the Kayu Ombun sub-district community. Lecturers from various concentrations in the field of law take turns explaining material and problems in everyday life related to law. Not only that, lecturers from the Faculty of Sharia and Law also opened a question and answer room for the public who were present at the counseling. The community enthusiastically asked questions to the speakers in the counseling.